2016
DOI: 10.1038/srep20949
|View full text |Cite
|
Sign up to set email alerts
|

Tackling amyloidogenesis in Alzheimer’s disease with A2V variants of Amyloid-β

Abstract: We developed a novel therapeutic strategy for Alzheimer’s disease (AD) exploiting the properties of a natural variant of Amyloid-β (Aβ) carrying the A2V substitution, which protects heterozygous carriers from AD by its ability to interact with wild-type Aβ, hindering conformational changes and assembly thereof. As prototypic compound we designed a six-mer mutated peptide (Aβ1-6A2V), linked to the HIV-related TAT protein, which is widely used for brain delivery and cell membrane penetration of drugs. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…66,67 Our simulations show a good correlation with experimentally data providing additional support for the use if this field amyloid type proteins. Recently, the ff99IDPs has been developed for IDP monomer simulation and demonstrate the good consistency with NMR data.…”
Section: Discussionsupporting
confidence: 73%
“…66,67 Our simulations show a good correlation with experimentally data providing additional support for the use if this field amyloid type proteins. Recently, the ff99IDPs has been developed for IDP monomer simulation and demonstrate the good consistency with NMR data.…”
Section: Discussionsupporting
confidence: 73%
“…The discovery of protective genetic variants like Aβ A2V and Aβ A2T , although rare, should prompt a novel vision of genetic studies, until now limited to the identification of pathogenic variants, expanding the genetic research into the detection of ‘protective’ DNA variations as useful grounds for the design of efficient disease-modifying therapies inmedicine [ 51 ].…”
Section: The Discovery Of An Autosomal Recessive Mutation In Admentioning
confidence: 99%
“…CD spectroscopy, SPR, and AFM showed that Aβ1-6 A2V inhibits acquisition of β-sheet secondary structure by full-length wt Aβ, elongation of wt Aβ amyloid fibrils and assembly of Aβ into amyloid fibrils, dramatically reducing the formation of protofibrils and filamentous structures[ 35, 51 ]. Moreover, toxicity studies on cellular models showed that Aβ1-6 A2V is not toxic on SY-SH5Y neuroblastoma cells even at high concentrations (20μM) and hampers the toxicity induced by Aβ1-42 wt on these cells [ 51 ]. Finally, to improve the translocation across the blood-brain barrier (BBB), we linked an amino acid sequence highly rich in basic residues (TAT) to the six-mer peptide so generating the Aβ1-6 A2V -TAT(D) compound.…”
Section: The Development Of a Potential Disease-modifying Therapyfor mentioning
confidence: 99%
See 2 more Smart Citations